Sandcastle beach - Holiday, Jenny (Romance author) (Holiday, Jenny (Romance author). Matchmaker Bay novel, 2021)
"Maya Mehta will do anything to save her tiny, beloved community theater. Put on musicals she hates? Check. Hire an arrogant former-pop-star-turned-actor? Done. But what Maya really needs to save her theater is Matchmaker Bay's new business grant. She's got some serious competition, though: Benjamin 'Law' Lawson, local bar owner, Jerk Extraordinaire, and Maya's annoyingly hot arch nemesis. Let the games begin. Law loves nothing more than getting under Maya's skin, and making those gorgeous eyes dance with irritation. But when he discovers the ex-pop star has a thing for Maya, too, Law decides he's done waiting in the wings--starting with a scorching-hot kiss. Turns out there's a thin line between hate and irresistible desire, and Maya and Law are really good at crossing it. But when things heat up, will they allow their long-standing feud to get in the way of their growing feelings?"--FantasticFiction.com.